Structural complexity and functional diversity of plant NADPH oxidases - Kaur, Gurpreet (Amino Acids, 2017)
Plant NADPH oxidases also known as respiratory burst oxidase homologs (Rbohs) are a family of membrane-bound enzymes that play diverse roles in the defense response and morphogenetic processes via regulated generation of reactive oxygen species. Rbohs are associated with a variety of functions, although the reason for this is not clear. To evaluate using bioinformatics, the possible mechanisms for the observed functional diversity within the plant kingdom, 127 Rboh protein sequences representing 26 plant species were analyzed. Multiple clusters were identified with gene duplications that were both dicot as well as monocot-specific. The N-terminal sequences were observed to be highly variable. The conserved cysteine (equivalent of Cys890) in C-terminal of AtRbohD suggested that the redox-based modification like S-nitrosylation may regulate the activity of other Rbohs. Three-dimensional models corresponding to the N-terminal domain for Rbohs from Arabidopsis thaliana and Oryza sativa were constructed and molecular dynamics studies were carried out to study the role of Ca(2+) in the folding of Rboh proteins. Certain mutations indicated possibly affect the structure and function of the plant NADPH oxidases, thereby providing the rationale for further experimental validation.